Controlled antibody release from gelatin for on-chip sample preparation12. Issue 10 (14th April 2016) - Zhang, Xichen; Wasserberg, Dorothee; Breukers, Christian; Terstappen, Leon W. M. M.; Beck, Markus
Abstract : Gelatin layers tailored for controlled release of antibody allow for optimized on-chip immunostaining of leukocytes in whole blood. Abstract : A practical way to realize on-chip sample preparation for point-of-care diagnostics is to store the required reagents on a microfluidic device and release them in a controlled manner upon contact with the sample. For the development of such diagnostic devices, a fundamental understanding of the release kinetics of reagents from suitable materials in microfluidic chips is therefore essential. Here, we study the release kinetics of fluorophore-conjugated antibodies from (sub-) μm thick gelatin layers and several ways to control the release time. The observed antibody release is well-described by a diffusion model. Release times ranging from ∼20 s to ∼650 s were determined for layers with thicknesses (in the dry state) between 0.25 μm and 1.5 μm, corresponding to a diffusivity of 0.65 μm 2 s −1 (in the swollen state) for our standard layer preparation conditions. By modifying the preparation conditions, we can influence the properties of gelatin to realize faster or slower release. Faster drying at increased temperatures leads to shorter release times, whereas slower drying at increased humidity yields slower release. As expected in a diffusive process, the release time increases with the size of the antibody. Moreover, the ionic strength of the release medium has a significant impact on the release kinetics. Applying these findings to cell counting chambers with on-chip sample preparation, we can tune the release to control the antibody distribution after inflow of blood in order to achieve homogeneous cell staining.